Organizational Legitimacy, Social Responsibility, and Employee Loyalty: The Role of Social Capital Mediation at Universitas Swadaya Gunung Jati - Nabila Alissya Putri; Sandi Nasrudin Wibowo (Politeknik Siber Cerdika Internasional, 2026)
Background: In higher education, faculty loyalty is an important factor in institutional sustainability. However, loyalty is influenced not only by individual internal factors but also by organizational legitimacy and socially responsible practices. In addition, the role of social capital as a bridge between social relationships and trust is believed to have the potential to strengthen this influence. Objective: This study examines the direct and indirect effects of organizational legitimacy and social responsibility on employee loyalty and investigates social capital as a mediating variable in the context of higher education. Methods: This study collected data from 113 respondents, including faculty members and staff at Universitas Swadaya Gunung Jati, using an associative quantitative approach through questionnaires. Data analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) method. Results: Organizational legitimacy and social responsibility were shown to have a positive and significant effect on employee loyalty, both directly and indirectly through social capital. Furthermore, social capital was found to effectively mediate this relationship. Conclusion: Organizational legitimacy and social responsibility can be optimized through the strengthening of social capital. Therefore, university management needs to strengthen trust, cooperation, governance transparency, and the maintenance of high-quality human resources.